Peace in the Face of Aggression : Responses to Aggression, Invasion, and War - Lewis, Court D., (Religious Studies, Theology and Philosophy E-Books Online, Collection 2026., 2025)
Peace in the Face of Aggression seeks to find ways to promote peaceful, nonviolent transitions in all arenas of common life, by examining the peaceful and nonviolent solutions to the Russo-Ukrainian War, Israeli-Palestinian War, and other current states of aggression. Authors were asked to reflect and provide arguments related on a variety of peaceful, nonviolent responses one might have to aggression and war, and the results have been organized around three main themes: 1) issues related to the frontline of conflicts; 2) issues related to the home front, specifically how the home front responds to war; and 3) issues related to interstate relations during acts of aggression and war.